Are children as relatives our responsibility? – How nurses perceive their role in caring for children as relatives of seriously ill patients. (December 2016) - Golsäter, Marie; Henricson, Maria; Enskär, Karin; Knutsson, Susanne
Abstract: Purpose: The purpose of this study was to elucidate how nurses perceive their role in caring for children as relatives to a parent with a serious physical illness. Method: A qualitative explorative design with focus group interviews was used. In total, 22 nurses working at one neurological, one haematological and two oncological wards were interviewed. The transcripts from the interviews were analysed in steps in accordance with inductive qualitative content analysis. Results: This study revealed six variations in how nurses perceived their role in the encounter with child relatives, ranging from being convinced that it is not their responsibility to being aware of the children's situation and working systematically to support them. Conclusion: Nurses should consider whether their patients have children who might be affected by their parent's illness. The nurses' self-confidence when meeting these children must be increased by education in order to strengthen their professional role. Furthermore, guidelines on how to encounter child relatives are required. Highlights: Nurses must establish whether their patients have children in order to support them. Guidelines on how to meet children who are relatives are needed to provide family-centred care. The nurses' self-confidence when meeting children as relatives must be increased.